Emerging Frontiers in Biomedicine: A 2025 Outlook on Transformative Research Themes - Alkhatib, Ahed J (International Journal of Molecular Microbiology, 2025)
Biomedicine is developing quickly, as a result of technological innovation, molecular science and computing power. Hot topics for research, grant applications and translation effort in the year 2025. This paper illustrates some of the fastest growing fields of biomedicine including the area of health artificial intelligence, genomics and precision medicine, regenerative therapies, cancer immunotherapy, the microbiome and neurobiological interfaces. Each theme is scientifically underpinned, clinically applicable, ethically considered and future proofed. This synthesis will give researchers, clinicians, and policymakers a strategic perspective on where biomedicine might go, and what public health and personalized medicine benefits these advances might offer.